2011
DOI: 10.1111/j.1365-2486.2011.02551.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying small‐scale deforestation and forest degradation in African woodlands using radar imagery

Abstract: Carbon emissions from tropical land‐use change are a major uncertainty in the global carbon cycle. In African woodlands, small‐scale farming and the need for fuel are thought to be reducing vegetation carbon stocks, but quantification of these processes is hindered by the limitations of optical remote sensing and a lack of ground data. Here, we present a method for mapping vegetation carbon stocks and their changes over a 3‐year period in a > 1000 km2 region in central Mozambique at 0.06 ha resolution. L‐band … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
147
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(154 citation statements)
references
References 56 publications
4
147
1
2
Order By: Relevance
“…In contrast, upscaling our finer scale AGWB estimations in both the RBCMA and DR did not produce large overestimation compared to the same local reference values (+8.1% and +4.5%, respectively, for MBE500 and 10.7% and 0.04% for the MBE1000). Similar findings are observed in [63], where Hill et al find considerable differences in mean AGWB by comparing between the biomass maps produced by [23] and [17] for a small study area in Mozambique (~1160 km 2 ), which is dominated by Miombo woodlands (mean AGWB ~35.6-38.4 tha −1 found in [23] vs. 102.4 tha −1 found in [17]). These findings confirm the need for caution when using biomass estimations produced from satellite EO [63] at coarse resolution for quantifying AGWB locally.…”
Section: Figuresupporting
confidence: 67%
See 1 more Smart Citation
“…In contrast, upscaling our finer scale AGWB estimations in both the RBCMA and DR did not produce large overestimation compared to the same local reference values (+8.1% and +4.5%, respectively, for MBE500 and 10.7% and 0.04% for the MBE1000). Similar findings are observed in [63], where Hill et al find considerable differences in mean AGWB by comparing between the biomass maps produced by [23] and [17] for a small study area in Mozambique (~1160 km 2 ), which is dominated by Miombo woodlands (mean AGWB ~35.6-38.4 tha −1 found in [23] vs. 102.4 tha −1 found in [17]). These findings confirm the need for caution when using biomass estimations produced from satellite EO [63] at coarse resolution for quantifying AGWB locally.…”
Section: Figuresupporting
confidence: 67%
“…In Africa, [21] created an ALOS PALSAR mosaic at 100-m spatial resolution to be used, among other applications, to map deforestation and agricultural encroachment upon the forest-savanna boundary. In their study within savanna landscapes, [22] identified strong relationships between AGWB and radar backscatter sensed by ALOS PALSAR, concluding that the approach was necessary and sufficient for monitoring and reporting of biomass baselines for REDD+ projects, and [23] similarly found ALOS PALSAR images to assist in quantifying deforestation at small scales in savanna woodlands in Mozambique. In Australia, [24] stressed the value of ALOS PALSAR data for quantifying the contribution of the woody component of tropical savannas to regional carbon stocks.…”
Section: Mapping Of Savanna Woodlands With Active Satellite Earth Obsmentioning
confidence: 99%
“…These should therefore be investigated over the study period to assess their magnitude of contribution to the biomass dynamics depicted by the change results. A study by [32] suggested correction of effects of moisture to L-band SAR backscatter recalibration of backscatter to ground data at each time point.…”
Section: Distribution Of Woody Biomassmentioning
confidence: 99%
“…Relevant studies by [39] utilized multi-temporal and dual-pol SAR in assessing structural components of the vegetation within KNP. The capability of L-band SAR backscatter intensity in quantifying small-scale forest degradation in the Miombo woodlands of Mozambique over a three-year period was demonstrated in [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation